The preliminary cytotoxicity study: anti-proliferative activity of aqueous extract of clinacanthus nutans, strobilanther crispa and pereskia bleo on oral squamous carcinoma cells orl-48 / Rahayu Zulkapli and Fathilah Abdul Razak. - Zulkapli, Rahayu; Abdul Razak, Fathilah (2019)
This in vitro study was carried out to screen the aqueous extracts of selected local plants (clinacanthus nutans, strobilanther crispa and pereskia bleo) known locally to possess anticancer properties for cytotoxic activity. Method: The antiproliferative activity on human oral squamous cell carcinoma, ORL-48 was assessed based on a colorimetric assay using neutral red dye. Result: Clinacanthus nutans exhibited an IC50 of 49.8 ± 0.02 µg/mL on ORL-48 cells, while Strobilanther crispa and Pereskia bleo showed no antiproliferative response. Conclusion: The aqueous extract of clinacanthus nutans, strobilanther crispa and pereskia bleo does not possess anti proliferative activity towards oral squamous carcinoma cells ORL-48.